THE JATULIAN (LOWER PROTEROZOIC) CARBONATES WITH ABNORMALLY HEAVY CARBON: STRATIGRAPHIC POSITION AND PALEOGEOGRAPHIC DISTRIBUTION IN THE BALTIC SHIELD - Heiskanen K.I.; Rychanchik D.V. (My University, 1999)
Vertical and lateral variations of δ13C and δ18O in the Lower Proterozoic (2.3-2.0 Ga) carbonates of the Baltic Shield are analyzed on the basis of carbon and oxygen isotope measurements in 460 Jatulian rock samples. The most heavy carbon isotope composition (δ13C > 10‰) is recognized in the Middle and basal Upper Jatulian parts of carbonate sequences (lower beds of the Upper Jatulian according to the two-member subdivision scheme). Accumulation age limits for carbonates with abnormally heavy C-isotope composition are estimated to be 2.25 and 2.08 Ga; the peak values of this isotopic parameter are confined to 2.12-2.10 Ga. The maximum average values estimated for lateral distribution of δ13Ccarb are concentrated in deposits of the axial zone of the Jatulian basin and decrease toward its periphery down to δ13C < 5‰. Any section with carbonates yielding the abnormally heavy C-isotope composition appears to be correlative with the Jatulian interval. The opposite statement, that a section where carbonates of this kind are missing cannot be correlated with this interval, is incorrect. The established peculiar geographic distribution of δ13C and δ18O in carbonates of the Baltic shield suggests that similar distribution patterns may be characteristic of other regions with Precambrian rocks. These distribution patterns were apparently controlled by geodynamic and paleogeographic factors in the course of the planet evolution.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой